Computational Forensics Third International Workshop, IWCF 2009, The Hague, The Netherlands, August 13-14, 2009, Proceedings - Geradts, Zeno J. M. H.; Franke, Katrin; Veenman, Cor J. (Image Processing, Computer Vision, Pattern Recognition, and Graphics, 2009)
This book constitutes the refereed proceedings of the Third International Workshop, IWCF 2009, held in The Hague, The Netherlands, August 13-14, 2009. The 16 revised full papers presented were carefully reviewed and are organized in topical sections on speech and linguistics, fingerprints, handwriting, documents, printers, multimedia and visualization. This volume is interesting to researchers and professionals who deal with forensic problems using computational methods. Its primary goal is the discovery and advancement of forensic knowledge involving modeling, computer simulation, and computer-based analysis and recognition in studying and solving forensic problems.